Ribosomal DNA analysis of three Phytophthora species occurring in India - and M. ANANDARAJ*, C. SHEJI, S.G. RENU, S. BALAJI (Indian Phytopathology, 2009)
Three Indian Phytophthora isolates from black pepper, coconut and cardamom were characterized based on internal transcribed spacer (ITS) regions of ribosomal DNA (rDNA). The sequence analysis and the predicted secondary structure of RNA of these species of Phytophthora revealed that black pepper isolate of Phytophthora shares characteristics of both P. capsici and P. tropicalis whereas coconut and cardamom isolates matched that of P. palmivora and P. meadii respectively.